Dampak Kebijakan Tarif Impor Terhadap Ekonomi Kedelai Indonesia - Laily, Dona Wahyuning; Roidah, Ida Syamsu; Purnamasari, Ika (Kadiri University, 2021)
Soybean is the main crop of the palawija system which is commonly applied in Indonesia. In the national economic system, soybean is a commodity owning strategic values due to its ability to supply nutrients needed by the community and a source of income for farmers. Demand for soybean is likely to continue to increase in line with population growth, increase in per capita income, increase in public awareness of nutritional adequacy, and the development of livestock preparation and silage industries. Given the high trend of soybean demand in the future, efforts to increase domestic soybean production are becoming increasingly important. Meanwhile in the future, the policy to protect domestic soybean farmers will be limited due to the demands of free trade. Considering that soybean is consumed in the form of processed food, the increasing demand for soybeans in the future indicates that there will be more opportunities for the development of home industries to produce this food. The need for soybeans as raw material for agro-industry cannot currently be met by domestic soybean production, both in terms of quality and quantity. This causes the need for imported soybeans to be even greater. Domestic soybean production, both in quality and quantity, seems to be unable to meet the soybean needed for industrial raw materials, thus causing a higher tendency for imported soybean demand. Therefore, import tariff policies in the face of world trade liberalization must be regulated in such a way by taking into account the interests of producers, consumers, and the government. This policy is still needed in realizing the independence of export quality soybeans. Kedelai adalah tanaman utama Sistem Palawija yang umum diterapkan di Indonesia. Dalam sistem perekonomian nasional, kedelai menjadi komoditas yang memiliki nilai strategis karena memiliki kemampuan untuk memasok hara yang dibutuhkan oleh masyarakat dan merupakan sumber pendapatan bagi petani. Permintaan kedelai akan terus meningkat seiring dengan adanya peningkatan jumlah penduduk, pertambahan pendapatan perkapita tiap penduduk, meningkatnya kesadaran masyarakat akan gizi yang cukup, serta berkembangnya industri persiapan dan silase ternak. Melihat masih tingginya trend permintaan kedelai di masa datang, upaya peningkatan produksi kedelai di dalam negeri menjadi semakin penting. Sementara itu di masa depan kebijaksanaan untuk melindungi petani kedelai di dalam negeri semakin terbatas peluangnya karena tuntutan perdagangan bebas. Mengingat sebagaian besar kedelai dikonsumsi dalam bentuk bahan pangan olahan, meningkatnya permintaan kedelai di masa depan menunjukkan semakin terbukanya peluang pengembangan industri rumah tangga untuk memproduksi bahan pangan tersebut. Kebutuhan akan kedelai sebagai bahan baku agroindustri saat ini tidak dapat dipenuhi oleh produksi kedelai dalam negeri baik dari segi kualitas maupun kuantitas. Hal ini menyebabkan kebutuhan akan kedelai impor akan semakin besar. Kedelai yang dibutuhkan untuk bahan baku industri tampaknya tidak dapat dipenuhi oleh produksi kedelai dalam negeri, baik kualitas maupun kuantitasnya, sehingga menyebabkan kecenderungan permintaan kedelai impor semakin tinggi. Oleh karena itu, kebijakan tarif impor dalam menghadapi liberalisasi perdagangan dunia harus diatur sedemikian rupa dengan memperhatikan kepentingan produsen, konsumen, dan pemerintah. Kebijakan ini tetap diperlukan dalam mewujudkan kemandirian kedelai kualitas ekspor.